Additional file 2 of Genomic evidence for sulfur intermediates as new biogeochemical hubs in a model aquatic microbial ecosystem - Adrien Vigneron (10162165); Perrine Cruaud (10162168); Alexander I. Culley (10162171); Raoul-Marie Couture (10162174); Connie Lovejoy (10162177); Warwick F. Vincent (10162180) (2021)
Additional file 1: Supplementary Figure S1. Heatmap representing the bacterial community composition in each sample determined using 16S rRNA gene (D), 16S rRNA (R) and 16S rRNA reads recovered from metagenomic data (M). Results of the two duplicate samples are shown for 16S rRNA gene and 16s rRNA. Only lineages with relative abundance >1% in at least one sample are shown. The right part of the graph represents the bacterial 16S rRNA gene quantification in the duplicate samples (blue bars), as well as the relative proportion between bacteria and archaea determined by 16S rRNA gene qPCR quantification (D; red bars) and in the metagenomic dataset (M; purple bar).